Imagining unity: the construction of an Imaginary of 'unity in diversity' in the decorative programme of the Northern Cape Legislature building - Freschi, F. (Southern African Humanities, 2021)
Using the Northern Cape Legislature complex (2004) as a case study, this paper considers the role that the architecture of public buildings - more particularly, the decorative programmes in these public buildings - is playing in the construction of a national imaginary of 'unity in diversity' in contemporary South Africa. Historically, the construction of great national buildings has always been closely allied to the construction of national identity. Such buildings, like the grandiose monuments that were their natural corollary, expounded the cultural and historical virtues and triumphs of the nation state, and thus aided in creating out of fraught geo-political 'space' the unified 'place' of nationhood. Recent commentators however, have shown how, in the context of increasing postnationalism in the developed, postmodern world, this link between architecture and nationalism is no longer as clear as it once may have been. Architecture is increasingly open to different forms of codification, and has in effect become 'an open space in which many conflicting projects struggle' (Delanty & O'Mahony 2002: 172). The South African situation presents an interesting case study in this regard.